Patient‐reported outcomes among patients with systemic mastocytosis in routine clinical practice: Results of the TouchStone SM Patient Survey. Issue 20 (23rd August 2022) - Mesa, Ruben A.; Sullivan, Erin M.; Dubinski, David; Carroll, Brittany; Slee, Valerie M.; Jennings, Susan V.; Finnerty, Celeste C.; Bohannon, Linda S.; Mathias, Susan D.; Lahue, Betsy J.; Castells, Mariana C.
Abstract : Background: Systemic mastocytosis (SM) is a rare clonal neoplasm driven by KIT D816V and other mutations. Data were collected from the patient perspective on disease burden and included an SM‐specific symptom assessment tool. Methods: US adults aged 18 years and older with a self‐reported SM diagnosis completed an online TouchStone SM Patient Survey of 100 items, including the 12‐item Short‐Form Health Survey, the Indolent Systemic Mastocytosis Symptom Assessment Form, and the Work Productivity and Activity Impairment Questionnaire, as well as questions about SM diagnosis, the impact of SM on daily activities, work impairment, and health care use. The results were analyzed using descriptive statistics. Results: Fifty‐six individuals completed the survey (89% women; median age, 48 years; mean time since diagnosis, 6.7 years), reporting indolent SM (66%), aggressive SM (9%), smoldering SM (5%), and unknown SM subtype (18%). Over a 1‐year recall, respondents reported seeking emergency care for anaphylaxis (30%) and taking three or more prescription medications (52%) for SM. Over one half of patients (54%) reduced their work hours because of SM, and 64% avoided leaving home because of symptoms. A majority of respondents (93%) had experienced ≥10 SM‐related symptoms, noting that the most bothersome were anaphylactic episodes (18%), abdominal/stomach pain (16%), diarrhea/loose stools (13%), and fatigue (11%). Whereas an Indolent Systemic Mastocytosis Symptom Assessment Form‐derived total symptom score of 28 is used to indicate moderate‐to‐severe symptoms, the mean total symptom score was 52.7. Mental and physical component summary scores from the 12‐item Short‐Form Health Survey were below population norms. Conclusions: Patients who were surveyed reported substantial symptom burden and unmet needs because of SM, as evidenced by seeking emergency care and reporting bothersome symptoms, poor quality of life, and reduced work hours and productivity. Lay summary: The objective of this research was to understand the burden and unmet needs in the rare disease of systemic mastocytosis (SM) to guide future care. Fifty‐six patients completed an online survey containing questions about their diagnosis, medications, health care use, quality of life, and SM symptoms. The results demonstrated that SM is associated with severe and burdensome symptoms, anaphylactic events, emergency department visits, use of multiple medications, reduced ability to work, and poor physical and psychological quality of life. These findings suggest the need for future advances to address unmet needs in patients affected by SM. Abstract : Systemic mastocytosis is associated with burdensome symptoms that negatively affect quality of life. Nonadvanced systemic mastocytosis is associated with significant symptom burden.